TEACHING ACCORDING TO THE CHILD’S ABILITY: INDIVIDUALIZED METHODOLOGICAL INSTRUCTION IN MUSIC AND ART EDUCATION — FOCUS ON THE STUDENT, NOT THE CLASS - Abdurayimov Faxriddin Muxammadali o‘g‘li, (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Annotation: This article explores the importance of student-centered instruction in music and art education, emphasizing the need to tailor teaching methods to each child’s unique abilities, pace, and learning style. It argues for a shift from traditional class-based instruction to individualized learning, where pedagogical decisions are based on the needs and potential of the learner rather than standardized expectations. The article highlights effective strategies for adaptive music teaching, addresses the psychological and developmental factors involved, and presents the benefits of a personalized approach in fostering creativity, motivation, and long-term engagement.